Impact of Non-Formal Education in the Development of Digital Literacy: A Mixed Method Research in the Khulna Region - Islam, Md Hamim (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the study: The aim of the study is to determine the effectiveness of Non-Formal Education programs in enhancing digital literacy, the issues faced by learners, and the possibilities to reinforce NFE-based digital literacy programs. Methodology: The study used a mixed-methods explanatory sequential design that involved a combination of quantitative data (218 NFE participants who were sampled using a stratified random sample) and qualitative data (20 participants purposely sampled). Survey questionnaires and semi-structured interviews were used. Quantitative data were analyzed through descriptive statistics and qualitative data were analyzed through thematic analysis. Main Findings: Results show that NFE programs have a substantial positive effect on digital literacy, especially basic computer skills, internet navigation, and social media skills, and data analysis skills among a relatively small number of learners. The participants indicated increased employability and real-world digitalization consistent with the principles of experiential and transformative learning. Nevertheless, systemic challenges such as insufficient equipment, poor internet connectivity, the inconsistency of the teaching standards, and insufficient post-training care remain the obstacles to overall fair digital learning experiences. Novelty/Originality of this study: The present study incorporated mixed-method evidence to unveil the role of NFE as an effective avenue of digital inclusion among marginalized communities of Bangladesh It reveals gaps like a shortage of cybersecurity, social stigma, and post-training constraints and provides system-wide perspectives that contribute to current knowledge on digital literacy development in the non-formal education systems.